Evaluation of CD34 Expression in Central and Peripheral Giant Cell Granulomas and Aneurysmal Bone Cyst of Jaws by Immunohistochemistry - Reza Zare Mahmoodabadi; Narges Ghazi; Abdollah Javan Rashid; Amene Yekta (Mashhad University of Medical Sciences, 2022)
Introduction: The present study aimed to evaluate vascular density in giant cell lesions with different biologic behavior. Therefore, CD34 expression in central and peripheral giant cell granulomas and the aneurysmal bone cyst was evaluated by immunohistochemistry.Materials and Methods: A total of 15, 15, and 8 samples of PGCG, CGCG, and ABC were selected from the archives of the Dentistry School of Mashhad University and Ghaem Hospital, Mashhad, Iran, respectively. Immunohistochemical evaluation of CD34 expression was performed according to the manufacturer's instructions to assess microvessel density (MVD). MVD was calculated in five microscopic fields and the mean MVD of samples was evaluated. Findings were analyzed using t-test, ANOVA, and Pearson's correlation coefficient.Results: CD34 expression was 31.53, 31, and 26.40 in CGCG, ABC, and PGCG samples, respectively. Although the highest MVD was in CGCGs, no statistical difference was observed between the studied groups (0.270).Conclusions: According to the findings of the present study, evaluation of microvessel density with CD34 expression indicates no pathogenesis and different biological behavior of the studied groups. Therefore, further research seems necessary.